Penegakan Hukum terhadap Tindak Pidana Politik Uang oleh Calon Anggota Legislatif pada Pemilihan Umum 2024 di Provinsi Nusa Tenggara Timur: Studi Kasus: Putusan Pengadilan Tinggi Kupang Nomor 26/PID.SUS/2024/PT KPG - Alven Patrick Tanggo; Deddy R. Ch. Manafe; Rosalind Angel Fanggi (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
This study aims to find out and analyze law enforcement against money politics crimes by legislative candidates in the 2024 general election in East Nusa Tenggara Province. This research is a normative judicial legal research sourced from primary legal materials and secondary legal materials with a case approach and a legislative approach. Data collection in this study uses interviews and documentation Furthermore, the legal materials that have been collected are described in a qualitative descriptive manner in order to obtain a picture that can be understood clearly and directed to answer the problem. The results of the study show that (1) Money politics actors have not been fully held criminally accountable for what they have done. Law enforcers must provide criminal penalties to perpetrators who have fulfilled the elements of criminal responsibility fairly so that they can have a deterrent effect so that it is hoped that in the future money politics cases will be minimized. (2) The role of the Integrated Law Enforcement Center (Gakkumdu) in handling cases of violations of the 2024 simultaneous elections in East Nusa Tenggara Province is to resolve violations of election crimes.